2020
DOI: 10.1101/2020.08.05.238337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-Transcriptional Regulation of Antiviral Gene Expression byN6-Methyladenosine

Abstract: SummaryType I interferons (IFN) induce hundreds of IFN-stimulated genes (ISGs) in response to viral infection. These ISGs require strict regulation for an efficient and controlled antiviral response, but post-transcriptional controls of these genes have not been well defined. Here, we identify a new role for the RNA base modification N6-methyladenosine (m6A) in the regulation of ISGs. Using ribosome profiling and quantitative mass spectrometry, coupled with m6A-immunoprecipitation and sequencing, we identified… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Representative read coverage plots were shown for Ifit2 (Figure 4C), this gene gained an obvious m 6 A peak in 3'UTR in N67CInfected samples and the expression level was dramatically upregulated by N67C infection (Figure 4B), consistent with the data that m 6 A enriched in 3'UTR had a positive effect on gene expression (Figure 3E). A recent study showed that the translation of interferon-induced genes could be enhanced after m 6 A modification as the antiviral mechanism (35). Thus, it is conceivable that m 6 A modification on these genes may have a similar role in the immune response to malaria infections.…”
Section: Malaria Parasite Infection-induced M 6 a Modifications Repro...mentioning
confidence: 99%
“…Representative read coverage plots were shown for Ifit2 (Figure 4C), this gene gained an obvious m 6 A peak in 3'UTR in N67CInfected samples and the expression level was dramatically upregulated by N67C infection (Figure 4B), consistent with the data that m 6 A enriched in 3'UTR had a positive effect on gene expression (Figure 3E). A recent study showed that the translation of interferon-induced genes could be enhanced after m 6 A modification as the antiviral mechanism (35). Thus, it is conceivable that m 6 A modification on these genes may have a similar role in the immune response to malaria infections.…”
Section: Malaria Parasite Infection-induced M 6 a Modifications Repro...mentioning
confidence: 99%
“…promotes the production of interferon-stimulated genes (ISGs); however, Zhang's work indicated that YTHDF3 functions as a negative regulator of antiviral immunity by promoting the translation of FOXO3 mRNA (92, 93). METTL3, METTL14, and YTHDF1 promote the expression of interferon-induced transmembrane 1 (IFITM1), a well-known ISG (94). A recent study by You's group reported that m 6 A can stabilize IRF3 mRNA, and Zhu's group demonstrated that m 6 A can increase the stability of interferon-regulatory factor 7 (IRF7) mRNA (95,96).…”
Section: Conclusion and Expansionmentioning
confidence: 99%